Ratiometric fluorescence detection of silver ions using thioflavin T-based organic/inorganic hybrid supraparticles1. Issue 17 (7th September 2015) - Li, Yan-Yun; Zhang, Min; Lu, Ling-Fei; Zhu, Anwei; Xia, Fei; Zhou, Tianshu; Shi, Guoyue
<x xml:space="preserve">Abstract</x> A novel ratiometric fluorescent probe for detecting silver ions was developed using thioflavin T-based functional organic/inorganic hybrid supraparticles.